If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(x+4)-44=8-40
We move all terms to the left:
-6(x+4)-44-(8-40)=0
We add all the numbers together, and all the variables
-6(x+4)-44-(-32)=0
We add all the numbers together, and all the variables
-6(x+4)-12=0
We multiply parentheses
-6x-24-12=0
We add all the numbers together, and all the variables
-6x-36=0
We move all terms containing x to the left, all other terms to the right
-6x=36
x=36/-6
x=-6
| a(a^2-5a+25)=0 | | -1=-2/3x1 | | -5=1/3x-3 | | 5+2x=x^2+2x+1 | | 74x+40=600 | | -4=1/3x-3 | | 11x-20=10x+11 | | (5D-1)/6+2=(3+d)/6 | | -0.1x+5.54=-0.3x+6.74 | | -12=(4x-4)/10 | | 73498324x+5=4 | | x(3x-7,5)+3x(2,5-x)= | | Y=600*8x | | 10^4x=1200 | | -40=12x+18 | | 10^x=1200 | | 15/2x+5=7 | | 6a+1/2=10a-1/6 | | a+1/2a=99 | | 7x+19=37 | | 6x=48-2 | | 5x-1÷2x+3=6 | | x²=81 | | 2x-18+13+8=4x-29 | | x^2*(x^2-4)-8+2x^2=0 | | c+4c+9c+16c=1 | | 9b+85=130 | | 10/2y.y=1 | | 10/2yy=1 | | -18.7x+3.66=-19.3x | | -13x+14=-11x-8 | | 3x^2+6=90 |